1979
DOI: 10.1136/sti.55.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal colonisation by Neisseria gonorrhoeae and Neisseria meningitidis in black and white patients attending a venereal disease clinic.

Abstract: SUMMARY Pharyngeal colonisation by Neisseria gonorrhoeae and Neisseria meningitidis was studied in 2000 patients attending a venereal disease clinic. Of these patients, 64 % were white and 36% were black. The incidence of gonococcal infections was highest in the period from June to August. The incidence of genital or rectal infections or both was higher in the black patients. Pharyngeal colonisation by gonococci was present in 1 3 % of the patients. There were no significant associations between pharyngeal col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The unduly high frequency of meningococcal carriage in patients with gonorrhoea noticed by Willcox et all was confirmed by Rufli2 and Young et al,3 but not by Noble et al 4 Differences in reported results may be related to the type of population studied. Most of the patients studied in the sexually transmitted disease (STD) clinic at St Mary's were male homosexuals with a recent history of oral sexual intercourse.…”
supporting
confidence: 58%
“…The unduly high frequency of meningococcal carriage in patients with gonorrhoea noticed by Willcox et all was confirmed by Rufli2 and Young et al,3 but not by Noble et al 4 Differences in reported results may be related to the type of population studied. Most of the patients studied in the sexually transmitted disease (STD) clinic at St Mary's were male homosexuals with a recent history of oral sexual intercourse.…”
supporting
confidence: 58%
“…Racial differences in the colonisation by pathogenic bacteria have been found among patients for whom cultures for staphylococci and meningococci have been performed. [18][19][20] Colonisation by both these micro-organisms is more common in whites than in blacks contrary to what might be expected as a result of overcrowding or other factors associated with low socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…While all of these authors compare the frequency of gonococci present in the genitals and meningococci present in the pharynx one could also assume that high pharyngeal meningococcal carriage rates should be associated with an ele vated carriage rate for gonococci in the throat. But that is seemingly not the case, neither in a population not selected for VD reasons as the one analyzed here nor in VD patients as demonstrated by Noble et al [13], While these authors found meningococci in the pharynges of 9.5% of their 2,000 patients and gonococci in 1.3%, only 2 of the latter 27 patients at the same time harbored meningococci there.…”
Section: Discussionmentioning
confidence: 62%